2018
DOI: 10.1259/bjr.20180658
|View full text |Cite
|
Sign up to set email alerts
|

Imaging features of thalassaemia

Abstract: This article highlights the range of osseous findings that can be encountered as well as the imaging features of extramedullary haematopoiesis. As iron overload remains a major cause of morbidity and mortality in these disorders, we also discuss the MRI evaluation of hepatic and cardiac hemosiderosis, to aid in the optimization of iron chelation therapy. Future imaging use will be dictated by evolving clinical needs, such as in screening for emerging morbidities, including hepatic fibrosis and hepatocellular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Patients with β-thalassemia intermedia and major can develop postcranial lesions, including subperiosteal marrow proliferation and new bone formation that covers the entire outer costal surface (rib-within-rib), small compression fractures in vertebrae (Adamopoulos and Petrocheilou, 2020), and Erlenmeyer flask deformities affecting particularly the humerus and femurs (Gosein et al, 2019;Adamopoulos and Petrocheilou, 2020). These alterations are not visible in sk.485 and are also scarcely identified in other possible paleopathological cases as can be seen in Table 1 and in the five infants (ages from 3 to 9 months) and an 8-year-old child reported by Tayles (1996) with unspecified genetic anemias, dated from the 2nd century CE, from the Khuk Phanin Di site (Thailand).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with β-thalassemia intermedia and major can develop postcranial lesions, including subperiosteal marrow proliferation and new bone formation that covers the entire outer costal surface (rib-within-rib), small compression fractures in vertebrae (Adamopoulos and Petrocheilou, 2020), and Erlenmeyer flask deformities affecting particularly the humerus and femurs (Gosein et al, 2019;Adamopoulos and Petrocheilou, 2020). These alterations are not visible in sk.485 and are also scarcely identified in other possible paleopathological cases as can be seen in Table 1 and in the five infants (ages from 3 to 9 months) and an 8-year-old child reported by Tayles (1996) with unspecified genetic anemias, dated from the 2nd century CE, from the Khuk Phanin Di site (Thailand).…”
Section: Discussionmentioning
confidence: 99%
“…Multisystem evaluations should be done frequently to ensure any systemic involvement of the disease or progression. Based on any clinical suspicion, imaging is necessary to be done as in gallbladder and biliary tract imaging, cardiac MRI, abdominal ultrasonography to assess and determine the carrier systemic status [16].…”
Section: Diagnosis and Subtypes Of Thalassemiamentioning
confidence: 99%
“…Marrow hyperplasia represents the serious osseous alteration which are further characterized with medullary expansion, generalized cortical thinning, spreading of bone caliber, coarsened trabecular pattern, cancellous bone resorption as well as osteopenia, which may result in pathological fractures. (9,10) A study on the radiographic features of jaws and teeth in patients with thalassemia using orthopantomography resulted large bone marrow spaces widely found in the posterior mandibular region. (11) On top of that, the study also found most cases revealed canal mandibular loss, imbalance crown body length of mandibular incisor, thinning of lamina dura and inferior cortex.…”
Section: Introductionmentioning
confidence: 99%